Development of novel carriers for transdermal delivery of peptides - Namjoshi, Sarika M (Curtin University, 2009)
Recent developments in genetic engineering and biotechnology have resulted in anincrease in availability of therapeutic peptides and small anti-cytokines. Oraladministration is inappropriate as these molecules are unstable in the gastrointestinaltract and are subject to hepatic first-pass effect. Transdermal delivery is an attractivealternative as the skin exhibits less enzymatic activity and allows for a controlled,sustained local therapeutic drug concentration over a prolonged period of time.However, the skin’s lipophilic stratum corneum acts as a major barrier to thedelivery of hydrophilic molecules, including peptides, resulting in lack of efficacy ofthese compounds if applied topically. Considerable research effort has beenfocussed on the development of skin penetration enhancement techniques. However,many of these techniques have been limited by insufficient penetration enhancementand/or induced irritancy.We have investigated three approaches to enhance the delivery of peptides that havetherapeutic or cosmetic effect in the skin. These approaches include the use ofphysical energy to enhance the delivery of Alanine-Tryptophan (Ala-Trp), lipoaminoacid (LAA) conjugation to increase the permeability of a HNE inhibitor Ala-Ala-Pro-Val (AAPV) and a cosmetic peptide, acetyl hexapeptide-3 and cyclisation to enhancethe delivery of a core peptide (CP) which has anti-inflammatory activity.In vitro permeation studies across human epidermis were performed in Pyrex glassFranz-type diffusion cells. Ala-Trp was selected as a small molecular weight modeldipeptide to study the penetration enhancement effects of Dermaportation, which is anewly developed pulsed electro magnetic field (PEMF) technology. The dipeptidewas found to be unstable on exposure to skin at 37°C and Dermaportation (Pulsedelectromagnetic field technology) significantly increased the in vitro permeabilitycoefficient of Ala-Trp across human epidermis from 7.7 x 10-4 cm/h with passivediffusion to 1.94 x 10-2 cm/h with Dermaportation over an 8 h period.Dermaportation thus may provide an effective means of delivering molecules that arehighly susceptible to degradation like dipeptides, in higher amounts and in arelatively short duration.The effectiveness of coupling a short chain lipoamino acid to enhance transepidermaldelivery of a model human neutrophil elastase (HNE) inhibitor (Ala-Ala-Pro-Val) was assessed. The optimal conjugate structure for skin penetration andbiological activity of this therapeutic peptide with anti-inflammatory activity wasdetermined. In order to enhance the trans-epidermal delivery of the peptide,lipophilic derivatives with LAAs of chain length C6, C8, and C10 were prepared bysolid phase synthesis. Conjugation to a C6-LAA enhanced epidermal permeability ofthe tetrapeptide. Stereoselective permeation of the lipopeptide diastereomers acrossthe human epidermis was observed. The amount of C6(D)-LAA-AAPV (467.94μg/cm2) was significantly higher than C6(L)–LAA-AAPV (123.04 μg/cm2). Thesame was observed with C8(D)-LAA-AAPV. The effect of donor concentration andskin hydration on skin permeability of C8(D,L)-LAA-AAPV and C10(D,L)-LAAAAPVwas also assessed and it was observed that there was higher permeation ofC10(D,L)-LAA-AAPV at a higher donor concentration. The lipoamino acid conjugates were more stable than the native tetrapeptide and biological activity was retained after coupling of the tetrapeptide to C6, C8 and C10 LAA.A cosmetic peptide, acetyl hexapeptide-3 was coupled to individual diastereomers ofC12 (A)-LAA and C12 (B)-LAA. The preliminary study was designed to assess theeffect of coupling of a LAA of higher molecular weight on the transepidermalpermeation and accumulation of this hexapeptide. Accumulation of these peptides inthe skin was also quantified. Detectable amounts of C12(A)-LAA-hexapeptide-3 andC12(B)-LAA-hexapeptide-3 were not found in the receptor solution but higherquantities of these conjugates were found to be retained in the skin. The amount ofC12(B)-LAA-hexapeptide-3 (59.92 μg/cm2 ± 10.64) in the epidermis was highestfollowed by C12(A)-LAA-hexapeptide-3 (33.06 μg/cm2 ± 3.70) and acetylhexapeptide-3 (12.64 μg/cm2 ± 1.48).Lastly, skin permeability and in skin stability of an anti-inflammatory peptide (corepeptide: CP) and two analogues that have demonstrated improved biological efficacyand specificity: a cyclic peptide sequence (C1) and its linear sequence counterpart(C1-L) were assessed. The stability of C1 and C1-L was significantly higher ascompared to CP when placed in contact with skin at 37ºC. The epidermal penetrationof the core anti-inflammatory peptide improved after cyclisation. The order of Lastly, skin permeability and in skin stability of an anti-inflammatory peptide (corepeptide: CP) and two analogues that have demonstrated improved biological efficacyand specificity: a cyclic peptide sequence (C1) and its linear sequence counterpart(C1-L) were assessed. The stability of C1 and C1-L was significantly higher ascompared to CP when placed in contact with skin at 37ºC. The epidermal penetrationof the core anti-inflammatory peptide improved after cyclisation. The order of permeation of the analogues was C1>C1-L>CP after 48h and 6 days. The amount of peptide retained in the skin was higher after 48h as compared to 8h due to greater partitioning of these peptides in the skin.This work demonstrates the enhancement effects of these three techniques tooptimize the transdermal/topical permeation of therapeutic and cosmetic peptides.